Targeted metabolomics reveals bioactive inflammatory mediators from gut into blood circulation in children with NAFLD - Miyang Luo; Jiayou Luo; Atipatsa C. Kaminga; Jia Wei; Wen Dai; Yan Zhong; Ningan Xu; Xiongwei Li; Haixiang Zhou; Xiongfeng Pan (npj Biofilms and Microbiomes)
Abstract Altered gut metabolites are important for the inflammatory progression in children with NAFLD. Fecal and plasma samples were collected from 145 subjects including 53 non-alcoholic fatty liver (NAFL), 39 nonalcoholic steatohepatitis (NASH) and 53 obese controls. We performed G350 targeted integrative metabolomics using high performance liquid chromatography mass spectrometry for fecal and plasma analysis of NAFL, NASH, and obese children. We found 9 metabolites involved in metabolic reprogramming of inflammation in NAFLD, such as lipid, carbohydrate, amino acid metabolism, and TCA cycle pathway. Moreover, 7 inflammation-related metabolites could discriminate NAFLD severity by machine learning model. This study identified three novel elevated inflammatory pathogenic metabolites and the relationship between increased inflammation, may be involved in TLR5/MYD88/NFκB pathway. These findings reveal that specific inflammatory metabolites entering the blood circulation from the gut are associated with disease severity and inflammatory pathogenesis in children with NAFLD.